Day of the Dragon King - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 1998)
The magic tree house takes Jack and Annie back two thousand years to ancient China where they must find the original copy of an old legend before the Imperial Library is burned down by the evil Dragon King.
"A Stepping Stone book.".
L.A. Recommended Foreign Language.
3.0
3-6
Keywords: Magic -- Fiction; Time travel -- Fiction; Tree houses -- Fiction; Magic -- Fiction; Time travel -- Fiction; Tree houses -- Fiction; China -- History -- Han dynasty, 202 B.C.-220 A.D. -- Fiction; China -- History